In search of a meaningful set of macroregions for the "New Europe" - Marinella Terrasi (European Regional Science Association (ERSA), 2003)
This paper aims at showing that the new enlargement of EU borders calls for a revision of the principal spatial paradigm that has been used to analyze economic development processes up to now: the centre/periphery paradigm. More specifically, it is maintained that a new macrostructure must be identified for the EU economic space, on which to project development spatial strategies. The regional delimitations adopted for the INTERREG programs don't seem appropriate for this puropose, because they are identified in order to promote transnational cooperation rather than to control the spatial components of European integration. Our analysis moves off from the delimitation introduced in the Second Report on Economic and Social Cohesion of the European Commission, which distinguishes among central, peripheral and intermediate regions. An alternative delimitation in five macroregions is proposed that disaggregates both intermediate and peripheral regions in two subregions by introducing a North/South dimension. In so doing we adhere to the idea of K.Peschel (1981), according to which the distance variable reflects the influence of the past on the contemporary spatial pattern of production and trade, more than transportation and communication costs. In other words, distance could be interpreted as a proxy for the influence of historical, cultural and linguistic affinity. We proceed by comparing the two delimitations in terms of a key variable that conditions regional inequalities: productivity per employed worker. We use the data base of Cambridge Econometrics for 127 regions of 15 EU member states and 15 sectors in 1995 and 1999. By developing a variant of Shift-and-Share analysis, we are able to disaggregate the structural and differential components of productivity differences between and within macroregions. The results are quite different for the two delimitations considered. For the first one (Second Report on Cohesion) the greatest part of the variability of regional productivity (75%) is absorbed by the differential components within macroregions. For the alternative delimitation in five macroregions that we propose, both within- and between- macroregions differential components result important, absorbing respectively 40% and 42% of the same variability. We conclude that our delimitation represents a more meaningful basis to analyze European regional inequality problems. In the final part of the paper we try to identify some factors that could help to explain the differential components of productivity in European regions and macroregions, like human capital, infrastructure, urban development. References Peschel K. (1981), "On the impact of geographical distance on the interregional patterns of production and trade", Envinronment and Planning A, 13, 1981
Keywords: 330